Childhood Socioeconomic Status and Cognitive Aging: An Intersectional Life Course Perspective. (17th December 2021) - Reynolds, Addam; Greenfield, Emily; Moorman, Sara; Reyes, Laurent
Abstract: Greater childhood socioeconomic status (cSES) is associated with better later life cognition. Largely absent from this literature is how structural racism potentially influences this relationship. Guided by intersectional life course theory, we examined if the influence of cSES and region of schooling on later life cognitive outcomes differs among non-Hispanic White (NHW) and Black older adults. We used data from the 2010-2016 waves of the Health and Retirement Study for participants ages 65 and older in 2010. Using growth mixture modeling, we estimated the associations between race, cSES (parental education, social, and financial capital), and region of schooling at age 10 (southern versus not) on cognitive performance. Consistent with prior research, there was a main effect of race on cognitive performance levels (but not with decline over time), with lower scores among older Black adults, on average. Among NHWs, higher cSES was protective for later life cognition, especially for NHW participants from the South. Although Black older adults who attended school outside of the South had higher levels of cognitive performance than their counterparts who attended school at age 10 in the South, Black older adults who attended school outside of the South–regardless of cSES–still had lower average scores on cognition at baseline than the most disadvantaged NHW participants. This paper implicates the effects of structural racism on cognitive performance among older Black adults, indicating the need for heightened attention to structural racism within interventions for optimizing brain health and promoting equitable cognitive aging across the life course.